Urban transformation, episcopacy, and hagiography in Arles (4th-6th centuries) - Duarte Silva, Paulo; Silva, João Victor Machado da (Romanitas - Revista de Estudos Grecolatinos, 2023)
This article explores the broad theme of the relation between urban transformation and episcopal leadership in the fifth and sixth centuries, focusing on the city of Arles. After presenting an overview of Arles’ trajectory, regarding its economic centrality, political importance, and growing ecclesiastical leadership in the region, we turn to the Vita Caesarii Arelatensis to analyze the relationship between spatial references and episcopal power in the case of Caesarius of Arles. It is a hagiography dedicated to the bishop and produced in the late 540s, which has great repercussions in historical studies. Based on a comparison with the hagiographies of preceding bishops, we argue that the way the Vita Caesarii approaches space and memory indicates a significant change in the way episcopal power was exercised between the first decade of the 5th century and the middle of the 6th century, especially during the bishopric of Caesarius (502-542).